Bargaining: Power, Tactics, and OutcomesBargaining: Power, Tactics, and Outcomes, by Bacharach Samuel B. and Lawler Edward J.. San Francisco: Jossey-Bass, 1981, 234 pp., $15.95. - Hasle, Fred (Academy of Management Review, 1983)
This article presents a review of the books ?Bargaining: Power, Tactics and Outcomes,? by Samuel B. Bacharach and Edward J. Lawler.